2001
DOI: 10.1562/0031-8655(2001)074<0424:mopaio>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Melanin Offers Protection Against Induction of Cyclobutane Pyrimidine Dimers and 6–4 Photoproducts by UVB in Cultured Human Melanocytes¶

Abstract: The goal of this investigation was to correlate the melanin content in human pigmentary cells with the generation of UVB-induced photoproducts and to examine the relationship between the melanin content and the removal of the photoproducts. Cultured melanocytes from light-skinned individuals synthesized less melanin and produced more cyclobutane pyrimidine dimers and 6-4 photoproducts upon UVB exposure than did melanocytes from black skin. Tyrosine-stimulated melanogenesis provided protection against DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 26 publications
2
50
0
1
Order By: Relevance
“…In addition, skin susceptibility to so-called photoaging may inversely correlate with pigmentation of the skin (Wlaschek et al, 2001). In cultured melanocytes, melanin was shown to offer protection against induction of major DNA lesions by UVB (Barker et al, 1995;Smit et al, 2001) and UVAinduced membrane damage (Kwam and Dahle, 2003). A significant inverse correlation between baseline skin pigmentation and the extent of UV-induced DNA damage was also reported by an independent study (Tadokoro et al, 2003).…”
Section: Photoprotective and Antioxidant Propertiesmentioning
confidence: 82%
“…In addition, skin susceptibility to so-called photoaging may inversely correlate with pigmentation of the skin (Wlaschek et al, 2001). In cultured melanocytes, melanin was shown to offer protection against induction of major DNA lesions by UVB (Barker et al, 1995;Smit et al, 2001) and UVAinduced membrane damage (Kwam and Dahle, 2003). A significant inverse correlation between baseline skin pigmentation and the extent of UV-induced DNA damage was also reported by an independent study (Tadokoro et al, 2003).…”
Section: Photoprotective and Antioxidant Propertiesmentioning
confidence: 82%
“…XPG, FEN-1-XPG or FEN-1 transductants were exposed to a UV dose of 20 J/m 2 , and genomic DNA was isolated at various times thereafter. The DNA samples were then probed with monoclonal antibodies against the 6-4PPs (43,44). The disappearance of the signals for 6-4PPs over time indicates proper removal of these lesions by NER.…”
Section: Resultsmentioning
confidence: 99%
“…Melanocytes from light‐skinned individuals containing mostly pheomelanin produced around twice as many CPDs upon UV exposure than did melanocytes from black skin. Moreover, the quantity and quality of melanin revealed that eumelanin concentration correlated better with DNA protection than pheomelanin . Skin type I to type VI melanocyte cells were irradiated with UVB, and the levels of the photoproducts were determined immediately and after 6 and 24 h. The induction of the photoproducts was inversely correlated with the skin type as it was mitigated by increased eumelanogenesis.…”
Section: Melanin In Photodamagementioning
confidence: 99%